OPTIMALISASI OPERASI RAZIA MESUM DI KOST-KOSTAN OLEH SATUAN POLISI PAMONG PRAJA KOTA PALEMBANG DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Putri Ardiana; Atika Atika (Tazir, 2023)
ABSTRACT Acts or criminal acts that have recently occurred both among the general public and adolescents in the lecture environment and must be accounted for in accordance with the principle of legality, namely one of the immoral crimes. There are various kinds of immoral crimes, one of which is immoral acts in boarding houses and lodging. This is not an open secret among the public, but there are many teenagers who do it. Obscene acts committed by a pair of humans outside of a legal marriage relationship, it can be said to be adultery. The research method used is the field type method, namely Empirical Jurisdiction by using data collection techniques through field research (Field Research). The results of the research revealed that violators could be subject to punishment based on article 9 of Palembang City Regional Regulation number 2 of 2004 concerning the eradication of prostitution. According to Islamic Criminal Law, the punishment for violators of obscene acts is jarimah fornication. Adultery is divided into two, namely adultery muhsan, given the punishment of stoning and stoned to death, while fornication ghairu muhsan, given a hundred lashes and exiled to a place far from the population. Keywords: Optimization, Civil Service Police Unit, Nasty Raids Operation.